Pengembangan Media Flashcard tentang Sayur dan Buah sebagai Media Pendidikan Gizi pada Anak - Arnisam, Arnisam; Z, Izzayana (Universitas Baiturrahim, 2024)
The prevalence of lack of consumption of vegetables and fruits in Indonesia in 2018 is very high, namely 95.5%. Meanwhile, in the group of school-age children, the prevalence was higher, namely 96%. Aceh province has a prevalence of less consumption of vegetables and fruit, which is 20.61%. One way to prevent the lack of consumption of vegetables and fruit is by providing nutrition education through. The purpose of this development is to find out the competencies needed in development, find out expert assessments of Flashcard media, and find out the results of field trials on the quality of Flashcard media. The data collection method was carried out using the in-depth interview method to obtain the basis for the concept of developing Flashcard media. The development research procedure that became the reference for researchers in developing vegetable and fruit flashcard was ADDIE (Analysis, Design, Development, Implementation, Evaluation). The results of the media feasibility test by media experts were 93.3%, material experts were 84.7% and the teacher's assessment was 91.6%. The results of media trials on students at SDN 2 Mata Ie were obtained on a scale of ³ 3 .95 in the good category